2011
DOI: 10.1172/jci58200
|View full text |Cite
|
Sign up to set email alerts
|

Glial cells in the mouse enteric nervous system can undergo neurogenesis in response to injury

Abstract: The enteric nervous system (ENS) in mammals forms from neural crest cells during embryogenesis and early postnatal life. Nevertheless, multipotent progenitors of the ENS can be identified in the adult intestine using clonal cultures and in vivo transplantation assays. The identity of these neurogenic precursors in the adult gut and their relationship to the embryonic progenitors of the ENS are currently unknown. Using genetic fate mapping, we here demonstrate that mouse neural crest cells marked by SRY box-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
400
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(429 citation statements)
references
References 48 publications
26
400
2
1
Order By: Relevance
“…In the postnatal gut persistent bipotential progenitors can generate glial cells or neurons depending on certain physiological or pathological requirements (15)(16)(17). GDNF plays an important role in proliferation but also during cell differentiation, while ET3 stimulates the proliferative properties of GDNF but blocks its differentiating ability maintaining a constant pool of progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the postnatal gut persistent bipotential progenitors can generate glial cells or neurons depending on certain physiological or pathological requirements (15)(16)(17). GDNF plays an important role in proliferation but also during cell differentiation, while ET3 stimulates the proliferative properties of GDNF but blocks its differentiating ability maintaining a constant pool of progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…This population was initially supposed to be only capable of generating glia in vivo. Now it has been shown to be susceptible to regenerate neuronal loss caused by an insult though this replacement does not occur constitutively [16,17]. Nonetheless, it has been shown that intestinal neurogenesis occurs, and this is possibly at least in part to signaling through 5-HT4 receptors [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with findings from previous reports (Natarajan et al 1999;Lindley et al 2008;Metzger et al 2009;Hotta et al 2013) and again raised a question how to bridge the gap between limited migratory capacity of grafted cells and reasonably long distance for them to travel covering the aganglionic gut segments. Recently, several investigators from leading laboratories have shown that neurogenesis occurs in ENS of adult rodents ex vivo (Becker et al 2013) and in vivo (Liu et al 2009;Joseph et al 2011;Laranjeira et al 2011). Liu et al (2009) signaling and the more recent study utilizing genetic fate mapping has shown that Sox10-expressing common precursors contribute to neurogenesis in response to ENS injury (Laranjeira et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they have been shown to possess a neurogenic potential in vitro and in vivo even though they are restricted to a glial fate in their native environment. 11,12 Furthermore, enteric glia are also capable of performing the functions of oligodendrocytes and astrocytes when transplanted into the CNS. 13 Harnessing the plastic capabilities of enteric glia thus holds great promise for the development of cell-based therapies for many diseases but the conditions and factors involved remain to be identified.…”
Section: Heterogeneity Of Both Neurons and Glia In The Enteric Nervoumentioning
confidence: 99%